Polar state in polycrystalline BaSn0.3Ti0.7O3 thin film determined from ac- & dc-field studies. (3rd August 2021) - Surampalli, Akash; Prajapat, Deepak; Raj, Rakhul; Reddy, V. Raghavendra
Abstract: The present work reports polarization response and the effects of ac - & dc -fields on 30% Sn doped BaTiO3 polycrystalline relaxor thin films as a function of temperature. Apart from the low temperature frequency dispersion in dielectric data, a frequency independent local maxima in dielectric constant and a concomitant peak in dielectric loss at T * ∼ 245 K is observed, which is unusual of bulk relaxor systems. Below T *, dispersion in dielectric constant becomes quite evident showing signatures of non-ergodic behavior. Subsequently, the dielectric and polarization responses in ergodic (> T *) and non-ergodic (< T *) states are studied to determine the polar state in the system. The ac -field dependence of permittivity indicates the presence of domain like dynamics, predominantly in non-ergodic state. Field induced transition to ferroelectric state, both in ergodic and non-ergodic phases, is demonstrated from the dc -field studies. Further, the dc -field and polarization hysteresis studies reveal the system resembles that of anti-ferroelectric systems below T *, a possible signature for the existence of incommensurate polar regions. These experimental results put together, provides key insights in understanding the field effects of relaxor behavior in doped barium titanate systems.